2019
DOI: 10.1111/1348-0421.12728
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression analysis of MHCI and chemokines CXCR3 and CXCR4 gene from freshwater carp,Catla catla

Abstract: The immune system with large number of molecules protects the host against a plethora of continuously evolving microbes. Major histocompatibility complex (MHC) molecules serve as cardinal elements of the adaptive immune system responsible for the activation of the adaptive immunity in the host. The present study reports MHCI molecule in freshwater carp, Catla catla, and its differential expression in immunologically relevant tissues post-infection with Gramnegative and Gram-positive bacteria. The MHCI sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In Japanese flounder ( Paralichthys olivaceus ), relative high expression of MHC Iα was found in the whole blood, liver and gills (Wang et al., 2019). In carp ( Catla catla ), gills, skin and liver were the rich tissues of MHC Iα (Banerjee et al., 2019). In golden pompano, the MHC Iα was expressed the highest in the intestine, and relatively high in head kidney and gills (Cao et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japanese flounder ( Paralichthys olivaceus ), relative high expression of MHC Iα was found in the whole blood, liver and gills (Wang et al., 2019). In carp ( Catla catla ), gills, skin and liver were the rich tissues of MHC Iα (Banerjee et al., 2019). In golden pompano, the MHC Iα was expressed the highest in the intestine, and relatively high in head kidney and gills (Cao et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of reports showed that the expression of MHC Iα was up‐regulated by pathogen infection (Banerjee et al., 2019; Cao et al., 2017; Chen et al., 2020; Luo et al., 2014; Wang et al., 2019). In this study, the expressions of PfMHC Iα were detected after infection in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first time to report its function in teleost antiviral response, which regulates IFN expression mainly through MAPK3 and JAK/STAT pathways. These findings would expand our knowledge about the complex function of Cxcl12/Cxcr4 axis in teleost, which is a link between the innate and the adaptive immune system and play a key role to improve the adaptive immunity (22,93). Understanding the regulation mechanisms of Cxcl12/Cxcr4 signaling can provide useful information for disease control with effective immune protection in gibel carp.…”
Section: Discussionmentioning
confidence: 86%
“…In teleost fishes, cxcr4 and cxcl12 also show high expression in immune tissues ( 15 , 16 ). After virus or bacteria invasion, cxcr4 and/or cxcl12 are significantly up-regulated in Asian swamp eel ( Monopterus albus ) ( 17 ), rock bream ( Oplegnathus fasciatus ) ( 18 , 19 ), orange-spotted grouper ( Epinephelus coioides ) ( 20 , 21 ), freshwater carp ( Catla catla ) ( 22 ), and yellow croaker ( Larimichthys crocea ) ( 16 ). Therefore, cxcr4 and cxcl12 have been suggested as an important part in fish innate immune system ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The transcription of CXCR3 was induced by Streptococcus iniae , similar to S. agalactiae , in PBL and kidney of big‐belly seahorse (Priyathilaka et al , 2017). The mRNA level of Catla catla CXC R3 was increased by A. hydrophila in PBL, kidney and SP (Banerjee et al , 2019). After stimulated with Vibrio anguillarum (a gram‐negative bacterium similar to A. hydrophila ) and Poly(I:C), the mRNA level of CXCR3 in kidney and SP increased in large yellow croaker (Liu et al , 2017).…”
Section: Discussionmentioning
confidence: 99%